Desakralisasi Ritual Tolak Bala Dalam Perspektif Fenomenologis: Tradisi Masyarakat Desa Pardamean Baru Mandailing Natal - Lubis, Rayendriani Fahmei; Saleh, Idris (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2024)
The tolak bala tradition holds profound significance in the lives of Pardamean Baru Village residents in Mandailing Natal. Amidst the escalating forces of globalization and modernization, such traditions frequently confront formidable challenges that originate both externally and internally within the community itself. This study endeavors to employ a phenomenological approach to delve into the subjective meanings intertwined with the rejection of bad luck practices in Pardamean Baru Village. Research methodologies encompassed in-depth interviews with community leaders well versed in the tolak bala tradition, alongside participatory observations aimed at comprehending the social, cultural, and environmental milieu in which this tradition unfolds. Subsequently, the amassed data underwent qualitative analysis, focusing on individuals' comprehension and engagement with tradition, as well as its relevance in their daily lives. The findings reveal that the tolak bala tradition transcends mere religious observance, permeating diverse facets of Pardamean Baru Village. This tradition holds profound spiritual connotations, as the community perceives the ritualistic rejection of the bala as a safeguard against impending threats and calamities. Moreover, this practice fosters interpersonal bonds and fortifies the community’s collective identity. This study underscores the need to apprehend the internal viewpoints of communities to safeguard and perpetuate invaluable cultural legacies. By grasping the intrinsic meanings and imports embedded within the tolak bala tradition, it is envisaged that more efficacious strategies can be devised to uphold this tradition amid the flux of contemporary times. Furthermore, this study enriches the discourse within phenomenology and cultural anthropology by delineating human experiences within a nuanced cultural and spiritual backdrop.